2019
DOI: 10.1093/ons/opz194
|View full text |Cite
|
Sign up to set email alerts
|

Craniometrics and Ventricular Access: A Review of Kocher's, Kaufman's, Paine's, Menovksy's, Tubbs’, Keen's, Frazier's, Dandy's, and Sanchez's Points

Abstract: Intraventricular access is frequently required during neurosurgery, and when neuronavigation is unavailable, the neurosurgeon must rely upon craniometrics to achieve successful ventricular cannulation. In this historical review, we summarize the most well-described ventricular access points: Kocher's, Kaufman's, Paine's, Menovksy's, Tubbs’, Keen's, Frazier's, Dandy's, and Sanchez's. Additionally, we provide multiview, 3-dimensional illustrations that provide the reader with a novel understanding of the craniom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 27 publications
0
62
0
3
Order By: Relevance
“…However, this proposal was not widely adopted owing to the complexity of the procedures, and the associated damage to the skull base and structures. In this study, we approached the CSF space using a previously reported simple and common external ventricle drain technique (Morone et al 2019), and demonstrated that this procedure could successfully restore brain elasticity. Moreover, this TEIF procedure exhibited a low risk of formaldehyde exposure.…”
Section: Discussionmentioning
confidence: 92%
“…However, this proposal was not widely adopted owing to the complexity of the procedures, and the associated damage to the skull base and structures. In this study, we approached the CSF space using a previously reported simple and common external ventricle drain technique (Morone et al 2019), and demonstrated that this procedure could successfully restore brain elasticity. Moreover, this TEIF procedure exhibited a low risk of formaldehyde exposure.…”
Section: Discussionmentioning
confidence: 92%
“…Kocher's point provides access to the frontal horn of the lateral ventricle. This precoronal point is so located to be lateral to the SSS and always anterior to the primary motor area [13]. Keen's point is located in the posterior parietal surface, 2-3 cm superior and posterior to the ear's pinna.…”
Section: Craniometric Points For Ventricular Accessmentioning
confidence: 94%
“…The catheter is direct cephalic and perpendicular to the temporal cortex (Interactive Model 7). The trigone of the ipsilateral ventricle is located 4-5 cm below [13].…”
Section: Craniometric Points For Ventricular Accessmentioning
confidence: 99%
See 2 more Smart Citations